2010
DOI: 10.1111/j.1464-410x.2010.09509.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bariatric surgery on urinary and sexual function

Abstract: P < 0.0001). In females there were significant improvements in the ICIQ-SF ( P = 0.0008) and Quality of Life ( P < 0.0001) scores. For each kilogram lost there was a 0.05 improvement in the ICIQ score ( P = 0.03) in females. There were also postoperative improvements in all symptoms of UI and stress incontinence in females but urge incontinence worsened, when adjusted for weight loss. In males there was no improvement in UI with weight loss after LGB. There was no relationship with time and UI in either gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
4
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
(80 reference statements)
7
39
4
6
Order By: Relevance
“…A longer study of 10 years has shown a decline in erectile function most probably due to ageing 34 . A recent study has shown a significant effect at 3 months 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A longer study of 10 years has shown a decline in erectile function most probably due to ageing 34 . A recent study has shown a significant effect at 3 months 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Ranasinghe et al (24) performed laparosopic gastric banding in 653 female patients, and reported postoperative improvements in their ICIQ-SF scores. In our study, we also detected improvements in postoperative ICIQ-SF scores when compared with the preoperative values.…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system consists of 8 items, which are rated as mild (0-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) symptomatic. Severity of symptoms and their progression within a specific time period are compared.…”
Section: Ipss: Its Former Name Was American Urological Association Symentioning
confidence: 99%
“…In Brazil, about half of the adult population were overweight in 2008-2009, of which approximately 30% were obese 12 . Obese people are at a higher risk for developing various comorbidities: type II diabetes, dyslipidemia, cardiovascular and cerebrovascular diseases, coagulation disorders, degenerative joint disease, some types of cancer, sleep apnea and urinary incontinence 4,20 . Women suffering from obesity are more likely to develop urinary incontinence, especially when related to stress 7,16,23 .…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that weight reduction may be an effective treatment for urinary incontinence 24 . In obese, studies show that after massive, surgically induced weight loss, there is resolution or alleviation of the symptoms of urinary incontinence 14,15,20,22,26,27 . Urinary incontinence usually leads to withdrawal from social interaction, psychosocial frustrations and early institutionalization.2 Therefore, its diagnosis and treatment are particularly important in women with morbid obesity, contributing to the improvement of quality of life 1,13,17,20,26,27 .…”
Section: Introductionmentioning
confidence: 99%